Prothymosin Alpha: An Alarmin and More... - Samara, Pinelopi; Karachaliou, Chrysoula-Evangelia; Ioannou, Kyriaki; E. Papaioannou, Nikos; F. Voutsas, Ioannis; Zikos, Christos; Pirmettis, Ioannis; Papadopoulos, Minas; Kalbacher, Hubert; Livaniou, Evangelia; E. Tsitsilonis, Ourania; Voelter, Wolfgang (Current Medicinal Chemistry, 2017)
Background/Objective: Prothymosin alpha (proTα) is a ubiquitous polypeptide first isolated by Haritos in 1984, whose role still remains partly elusive. We know that proTα acts both, intracellularly, as an anti-apoptotic and proliferation mediator, and extracellularly, as a biologic response modifier mediating immune responses similarly to molecules termed as “alarmins”. Our research team pioneered the elucidation of the mechanisms underlying the observed activities of proTα. Results: We were the first to demonstrate that proTα levels increase during normal and abnormal cell proliferation. We showed that proTα acts pleiotropically, inducing immunomodulatory effects on immune cell populations. We revealed that the immunoreactive region of proTα is the carboxyterminal decapeptide proTα(100-109) and both molecules stimulate innate immune responses, signaling through Toll-like receptors (TLRs), specifically TLR-4. We reported that proTα and proTα(100-109) bind on the surface of human neutrophils on sites involving TLR-4, and cell activation is complemented by cytoplasmic calcium ion influx. Further, we showed that proTα and proTα(100-109) act as adjuvants upstream of lymphocyte stimulation and, in the presence of antigen, promote the expansion of antigen-reactive effectors. Most recently, we reported that proTα(100-109) may accumulate in experimentally inflamed sites and can serve as a surrogate biomarker in severe bacterial infections, proposing that extracellular release of proTα or proTα(100- 109) alerts the immune system during conditions of danger. Conclusion: We, therefore, suggest that proTα, and likely proTα(100-109), act as alarmins, being important immune mediators as well as biomarkers, and could eventually become targets for new therapeutic/diagnostic approaches in immune-related diseases like cancer, inflammation, and sepsis.
Keywords: inflammation